Modeling the long-term effect of temperature, rainfall, and solar radiation to rice productivity - Gonzaga, Myla Reambonanza (2011)
Three of the major climatic factors that affect the yield of rice are temperature, rainfall and solar radiation. This study attempted to develop a multiple regression model in each of the PAGASA stations: PCA, Davao, and USEP-Tagum. Comparison of means of each of the climate data was done to examine possible shift in the pattern over specified time horizon which could be attributed to climate change. 10 year interval was used for PCA, 2-year for Davao, and 3-year for USEP-Tagum. In the modeling, two sets of data were utilized. The first set was used for model formulation and the other one was for model validation. The result suggests that among the climatic factors considered, temperature had strong negative impact to the yield of rice for the three PAGASA stations. Solar radiation and rainfall were found to be directly proportional to yield but their contribution were not very significant. By comparing the means of the actual data, it was found out that there was a shift in the pattern of rainfall, solar radiation, and temperature in PCA PAGASA station. On the other hand, no shift was observed in Davao station while rainfall amount was the only climate factor that has significant shift in USEP-Tagum. This suggests that climate change was evident in PCA and USEP-Tagum PAGASA stations.